2012
DOI: 10.7314/apjcp.2012.13.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Profile, Clinical Presentations and Histopathological Features of Colo-rectal Cancer in Al Hassa Region, Saudi Arabia

Abstract: Background: Patients' demographics, presenting clinical and histopathological features for colo-rectal cancer (CRC) are important factors for patients' outcome and disease prognosis. This study aimed to describe the pattern of CRC in terms of patients' demographics, main presenting symptoms and histopathological features in Al Hassa region of Saudi Arabia. Subjects and Methods: A retrospective hospital records-based study which included reviewing of patients' records diagnosed with CRC at three general hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 11 publications
7
18
0
Order By: Relevance
“…These figures are in concordance with the studies done by Amin et al [4] in which the mean age was 54.8±14.5 and 63.5 years respectively. Gender proportion was more in favour of males irrespective of the age groups and tumor subtype with Male:Female ratio being 1.8:1.…”
Section: Resultssupporting
confidence: 82%
“…These figures are in concordance with the studies done by Amin et al [4] in which the mean age was 54.8±14.5 and 63.5 years respectively. Gender proportion was more in favour of males irrespective of the age groups and tumor subtype with Male:Female ratio being 1.8:1.…”
Section: Resultssupporting
confidence: 82%
“…Other factors affecting delay in diagnosis of colorectal cancer in our settings are poor knowledge of the symptoms, attitudes to screening as well as health care personnel failure to suspect colorectal cancer in patients presenting with a rectal bleeding (Hashim et al, 2010;Kong et al, 2010;Hashim et al, 2011). Advanced colorectal cancer disease in 2/3rd of the patients was also reported among patients in other Asian counties (Amin et al, 2012;Hajmanoochehri et al, 2014) Our younger (≤ 40 years) patients had significantly higher tumor grade compared to older age groups. This is in line with previous studies where colorectal cancers were found to be more aggressive, spread faster and are associated with a poor prognosis in younger age groups (Chou et al, 2011;Amin et al, 2012).…”
Section: Discussionsupporting
confidence: 70%
“…Advanced colorectal cancer disease in 2/3rd of the patients was also reported among patients in other Asian counties (Amin et al, 2012;Hajmanoochehri et al, 2014) Our younger (≤ 40 years) patients had significantly higher tumor grade compared to older age groups. This is in line with previous studies where colorectal cancers were found to be more aggressive, spread faster and are associated with a poor prognosis in younger age groups (Chou et al, 2011;Amin et al, 2012). The higher proportion of young Malays affected suggests that this section of the population may need to be screened at a younger age than the Asian Pacific guidelines suggest.…”
Section: Discussionsupporting
confidence: 70%
“…However, studies have not used 30 years as the age cut-off. In most of the published studies age limit for young onset rectal cancer is 40 years (Domergue et al, 1988;Liang et al, 2003;Amin et al, 2012;You et al, 2012). Kansakar and colleagues attempted to determine changing trends in etiopathology in colorectal cancer patients in Nepal.…”
Section: Discussionmentioning
confidence: 99%